Uji In-Vitro Penurunan Kadar Kolesterol dengan Perbandingan Tiga Dosis Kitosan Cangkang Kepiting Bakau (Scylla serrata) pada Suspensi Granul Effervescent - Novyanti, Erna Sri; Andina, Fateha Rizka; Subekti, Laura Andrea; Imtihani, Hilya Nur (Jurnal Ilmiah Medicamento, 2025)
Changes in human lifestyle—such as smoking, lack of physical activity, and poor dietary habits—have contributed significantly to the increasing incidence of hypercholesterolemia. Most cholesterol-lowering drugs currently available are chemically synthesized and may be associated with undesirable side effects. Consequently, there is growing interest in developing safer, natural alternatives. Indonesia produces a large volume of crab shell waste, which presents an opportunity for the sustainable production of chitosan, a biopolymer known for its cholesterol-lowering potential. However, chitosan has limited solubility in water, which can hinder its absorption and usability. To address this limitation, chitosan was formulated into an effervescent granule suspension to enhance solubility and improve patient compliance through easier consumption in liquid form. The effervescent granule suspensions were prepared using the wet granulation method. This study aimed to evaluate their cholesterol-lowering effects using the in vitro Lieberman–Burchard method, employing three different chitosan doses: F1 (45 mg), F2 (55 mg), and F3 (75 mg), in order to determine the optimal dosage. The average cholesterol reduction percentages were F1 = 14.66% ± 2.12, F2 = 22.39% ± 6.06, F3 = 13.37% ± 2.99, and simvastatin = 19.02% ± 0.74. Although F2 exhibited the highest cholesterol-lowering activity, the differences among the three formulations were not statistically significant (p = 0.156).